Epigenetics and Triplet-Repeat Neurological Diseases - Nageshwaran, Sathiji; Festenstein, Richard (Frontiers in Neurology, 2015)
The term “junk DNA” has been reconsidered following the delineation of the functional significance of repetitive DNA regions. Typically associated with centromeres and telomeres, DNA repeats are found in nearly all organisms throughout their genomes. Repetitive regions are frequently heterochromatinized resulting in silencing of intrinsic and nearby genes. However, this is not a uniform rule, with several genes known to require such an environment to permit transcription. Repetitive regions frequently exist as dinucleotide, trinucleotide, and tetranucleotide repeats. The association between repetitive regions and disease was emphasized following the discovery of abnormal trinucleotide repeats underlying spinal and bulbar muscular atrophy (Kennedy’s disease) and fragile X syndrome of mental retardation (FRAXA) in 1991. In this review, we provide a brief overview of epigenetic mechanisms and then focus on several diseases caused by DNA triplet-repeat expansions, which exhibit diverse epigenetic effects. It is clear that the emerging field of epigenetics is already generating novel potential therapeutic avenues for this group of largely incurable diseases.